PENGARUH PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. WIN WAHANA CIPTA MARGA - Debiyanti, Pabuntang; Kordiana, Sambara (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
This study aims to evaluate the effect of job training on employee performance at PT. Win Wahana Cipta Marga, a construction company in Makassar engaged in Hotmix and Ready Mix. Job training is recognized as one of the important factors in improving the quality of human resources, which in turn can affect employee performance and the achievement of company goals. The method used in this study involves collecting data through a questionnaire distributed to 30 employees from various positions in the company. The results of the validity and reliability test show that the instrument used is valid and reliable. However, the results of the correlation coefficient analysis showed that job training did not have a significant correlation with employee performance, with a correlation coefficient value of 0.199 which was included in the very low category. Thus, it can be concluded that job training at PT. Win Wahana Cipta Marga does not have a significant influence on employee performance.